2018
DOI: 10.1002/bit.26843
|View full text |Cite
|
Sign up to set email alerts
|

The pearl necklace model in protein A chromatography: Molecular mechanisms at the resin interface

Abstract: Staphylococcal protein A chromatography is an established core technology for monoclonal antibody purification and capture in the downstream processing. MabSelect SuRe involves a tetrameric chain of a recombinant form of the B domain of staphylococcal protein A, called the Z‐domain. Little is known about the stoichiometry, binding orientation, or preferred binding. We analyzed small‐angle X‐ray scattering data of the antibody–protein A complex immobilized in an industrial highly relevant chromatographic resin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…According to the shrinking core model, when the antibodies in a sample reach the adsorbent they bind to the first Protein A ligands at the surface of the beads with the subsequent molecules binding to the inner ligands until reaching the center of the particle. In a recent study we concluded that in the linear range of the isotherm, the antibodies would bind preferably to the outermost domains in an average stoichiometry of 1:1 or lower . Therefore, the reorientation/rearrangement of the molecules upon binding is more favorable than multilayer formation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the shrinking core model, when the antibodies in a sample reach the adsorbent they bind to the first Protein A ligands at the surface of the beads with the subsequent molecules binding to the inner ligands until reaching the center of the particle. In a recent study we concluded that in the linear range of the isotherm, the antibodies would bind preferably to the outermost domains in an average stoichiometry of 1:1 or lower . Therefore, the reorientation/rearrangement of the molecules upon binding is more favorable than multilayer formation.…”
Section: Resultsmentioning
confidence: 96%
“…Also, as mentioned, having multiple binding sites per Protein A ligand is a source of heterogeneous binding, with high‐ and low‐energy sites. So, the binding of antibody is likely a stochastic phenomenon in which the distribution of the binding energy determines the probability of concomitant binding events …”
Section: Resultsmentioning
confidence: 99%
“…To overcome these drawbacks manufacturers have continuously engaged in the design of novel resins with improved characteristics. MabSelect SuRe™, used in the capture step of Reblozyl® (activin receptor type IIB to treat beta thalassemia) and Alprolix® (a coagulation factor IX for hemophilia B), is a resin functionalized with a tetrameric chains of alkali-stabilized protein A-derived ligand (of the Z-domain of staphycoccal protein A) produced in E. coli ( Silva et al, 2018 ). This ligand is NaOH tolerant, allowing a deep cleaning of the resin after each purification round, minimizing cross-contamination, and extending the lifetime of the resin.…”
Section: Fc-fusionmentioning
confidence: 99%
“…Native Staphylococcus aureus protein A is a tetramer that, when stretched, has an approximate length of 10 nm, and a single domain length of ~3 nm (Protein Data Bank:1BDD [31]). Mazzer et al and Silva et al suggested the binding is usually at a 2:1 ratio [10,32] when used as an affinity chromatography ligand, whereas Plewka et al [17] estimated that antibodies bind to protein A molecules at a 1.2:1 ratio. They both agree however that the IgG molecules are bound to the protein A ligand at a tilted orientation near the resin surface [10,17].…”
Section: Protein a -Igg Bindingmentioning
confidence: 99%